Current status and progress in the treatment of congenital liver cyst - Chaoxing, Liao; Yuehua, Li; Jianping, Gong (International Surgery Journal, 2021)
Liver cyst is a relatively common benign liver disease. According to the cause of the disease, it can be divided into two types: non-parasitic liver cyst and parasitic liver cyst. Congenital liver cyst is the most common non-parasitic liver cyst in clinical practice, also known as true cyst, which mainly include simple liver cyst and polycystic liver diseases (PLD). In recent years, with the popularization of ultrasound and other examinations, the detection rate of liver cyst has increased year by year, but there is no unified consensus on the treatment of liver cysts. This article reviews the conservative treatment, puncture drainage, aspiration sclerotherapy, surgical treatment and other treatment options for congenital liver cysts, as well as the technological progress in recent years.